(untitled) - Dobrotková, Marta (Doprava a spoje, 2009)
From 1.1.2010, Slovakia will introduce an electronic toll collections on highways and first class roads. For this reason, it will be necessary to develop a matrix system of the toll rates for piece shipments, which would be offset by costs. The aim of this article was to show how the toll of an appropriate amount attributable to the shipment.